Photochemical Behaviour in Macrocyclic Copper Complex-Bromate-Malic Acid System - Hu, Lin; Zhang, YaQin; Yang, Xiancong; Li, BinBin; Xu, WenYuan; Hu, Gang (Asian Journal of Chemistry, 2014)
The photochemical behaviour in the macrocyclic copper complex-bromate-malic acid system was investigated in this paper. Macrocyclic copper complex [CuL](ClO4)2, where ligand L is 5,7,7,12,14,14-hexemethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene, is an enzyme-like complex. Experimental results indicated that the chemical oscillations exhibited ultrasensitive response to illumination, where the amplitude of oscillation were significantly changed but the frequency remained unaffected by ultraviolet light working at 245 nm with an intensity of more than 450 Lux. Increase in light intensity could enhance inhibition on the oscillations. At a constant illumination, the influences of light were examined with the variation of the concentration of bromate, malic acid, and macrocyclic complex. It was found that the ultraviolet light has affectedly influence on the oscillation trajectories of potentials of platinum electrode vs. those of bromide selective electrode.